Comparative description of the use of modern methods of hormonal contraception for women with excessive body mass - I. B. Gridina (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
Maintenance of reproductive health of women with excessive weight is the actual problem of nowadays and is an important direction of modern medicine.